KUALITAS NOODLE DARI KOMPOSIT PATI AREN (Arenga pinnata Merr.) DAN TEPUNG GARUT (Maranta arundinaceae L.) - , LAURENCIA LOLA KARLINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Arrowroot (Marantha arundinaceae L.) is rhizomes of the tropical plant which is spread in Indonesia. Arrowroot rhizomes need milling process before it is used for making noodles. Arrowroot flour should be mixed with other material that its potencies as raw material for making noodles have been known, thus the noodles have good quality same as commercial product. Arenga starch can be mixed with arrowroot flour because it has high amylose content. This research was purposed to investigate the effect of arrowroot flour substitution on the arenga starch noodle qualities which is included appearance, cooking properties, textural properties, and sensory properties. Four steps that were passed in this research are chemical and functional characterization of raw materials, noodle production, characterization of noodle qualities, and hedonic test of noodle. Chemical and functional characterization of raw material is included on proximate analysis, amylose and total starch analysis, swelling power, and solubility of arrowroot flour. Noodle was made with five variation of arenga starch:arrowroot flour (0:100, 25:75, 50:50, 75:25, 100:0). Characterization of noodles qualities are included on appearance, cooking properties, textural properties, and sensory properties. The results show us that arrowroot flour substitution affects noodle qualities such as color, brittleness, cooking time, cooking loss, swelling index, expantion ratio, tensile strength, elongation, and stickiness. Noodles that have characteristic nearest to the commercial products are the mixture of arenga starch:arrowroot flour (75:25) and (100:0). Composite noodle from the mixture of arenga starch:arrowroot flour (75:25) is the most favored product by panelist.